-4(x-10)=-8(x-5)

Simple and best practice solution for -4(x-10)=-8(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x-10)=-8(x-5) equation:


Simplifying
-4(x + -10) = -8(x + -5)

Reorder the terms:
-4(-10 + x) = -8(x + -5)
(-10 * -4 + x * -4) = -8(x + -5)
(40 + -4x) = -8(x + -5)

Reorder the terms:
40 + -4x = -8(-5 + x)
40 + -4x = (-5 * -8 + x * -8)
40 + -4x = (40 + -8x)

Add '-40' to each side of the equation.
40 + -40 + -4x = 40 + -40 + -8x

Combine like terms: 40 + -40 = 0
0 + -4x = 40 + -40 + -8x
-4x = 40 + -40 + -8x

Combine like terms: 40 + -40 = 0
-4x = 0 + -8x
-4x = -8x

Solving
-4x = -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-4x + 8x = -8x + 8x

Combine like terms: -4x + 8x = 4x
4x = -8x + 8x

Combine like terms: -8x + 8x = 0
4x = 0

Divide each side by '4'.
x = 0

Simplifying
x = 0

See similar equations:

| 4(x-3)=6-(x+4)+1 | | (x-5)=7x-27 | | 12y-3y-6=9 | | 8/9h=48 | | X/3-1=-5 | | 2f^2+8h+3=3 | | a/6-1=4 | | 9m-2=-26+5m | | 5t-16=-44+9t | | -10+2x=-2 | | 22d/2=14 | | 21x^2+5x-9=0 | | h=-16t^2+96t+880 | | Logs=3.1 | | 5x/4=16 | | 7m+4=24.28 | | (x+10)-(3x+12)=7x+12(11.4) | | z-18/-2=7 | | H=16t^2-16t+60 | | 3(x-2)=2-(x+3)+4 | | k+4=7k-4 | | 2x^2=13-6x | | log3x^2/12 | | 3(x-2)=(x+3)+4 | | 8-5(2x-7)=3x+11 | | 2R-1/5=1-2R/2 | | c^2+7c+16=0 | | 0=4x^2+9x-259 | | n+5=2x | | 18s/5=-11 | | 14-(5x-2)=2(x+8) | | x^5+x+3= |

Equations solver categories